KAJIAN TINGKAT BAHAYA EROSI DI BEBERAPA PENGGUNAAN LAHAN DI KAWASAN HILIR DAERAH ALIRAN SUNGAI (DAS) PADANG - Tomy Ardiansyah; Kemala Sari Lubis; Hamidah Sari Hanum (Jurnal Agroekoteknologi, 2013)
Study about erosion hazard level on some land uses was coducted at watershed of Padang. Thisresearch was implemented in the downstream Padang watershed of Tebing Tinggi region. theobjectiveof this research is to determine the tolerance erosion (T), actual erosion (A), and erosionhazard level at several land use in downstream areas DAS Padang. This research was conducted byusing survey method Sampling by cluster method at four (4) land uses consist of palm oil (twentyyears), rubber, cacao and cassava. Prediction of erosion by using USLE (Universal Soil LossEquation). The result showed that highest actual erosion at land rubber was 374.298 ton/ha/thn atundulating topography, lowest at cacao was 17.960 ton/ha/thn at flat topography, highest tolerancaerosion at cassava was 28.250 ton/ha/thn, lowest at rubber was 23.750 ton/ha/thn and level oferosion hazard highest at rubber was 15.760 ton/ha/thn at undulating topography included in thecriteria low, lowest at cacao was 0.718 ton/ha/thn at flat topography included in the criteria verylow.